Występek mieszkańców całej ziemi w świetle Księgi Rodzaju (11,1-9) - Adamczyk, Dariusz (Poznańskie Studia Teologiczne, 2011)
In Gn 11,1-2 the author presents the characters of the narrative. It is emphasized that at an unspecified time in the past there occurred a change in human lifestyle from a nomadic life to a settled one. People seek a space to live that would enable them to accomplish their plans. The next two verses show the whole humankind's sin of pride that consists in contradicting God. The author depicts it in a symbolic way as the building of a tower that would reach the heavens. The erected structure bears resemblance to Mesopotamian ziggurats - constructions that to the author of the narrative represent idolatrous cult. The tower is a symbol of the crowning achievement of human plans and misguided human ambitions that diverge from God's plans. Such a perspective is suggested in the story by God's reaction to the undertaking (verses 5-9). The moral judgment of the project is contained in the effects of divine punishment, which convey the truth that separation is the aftermath of sin. The phenomenon of organized evil described in the story is not so much a sum of the transgressions of individual humans as a sin of the entire human community.